Morphology and feeding biology of larvae of the South African endemic water beetle genus Prosthetops Waterhouse, 1879 (Coleoptera: Hydraenidae) - Delgado, Juan A.; Bilton, David T. (Zootaxa, 2024)
The larvae of three species of the South African endemic water beetle genus Prosthetops Waterhouse, 1879 are described and illustrated for the first time. The second and third instar larvae of Prosthetops nitens (Péringuey, 1892), as well as third instar larva of P. megacephalus (Boheman, 1851) and P. wolfbergensis Bilton, 2013, are treated here. These three species share a combination of morphological and chaetotaxic characters that can be used for positive identification of larvae of this genus: head capsule with pores FC1 present, second antennomeres with two well-developed distal sensory appendages, maxillary seta Cdo1 very reduced, thoracic subprimary setae Dd’ absent, subprimary setae Dc’ minute and inserted on the boundary between pretergal and tergal areas, urogomphi moderately separated at the base, anal lobe with well-developed dorsal, lateral and ventral plates, and a lack of anal hooks. Some insights on the gut-contents of the larva of P. wolfbergensis are offered and an unusual urogomphal malformation observed in a larva of P. nitens is also described and illustrated. These are the first described larvae of the subfamily Prosthetopinae, and their morphology is compared to that of other known hydraenid larvae.